PENGELOLAAN PEMBELAJARAN KIMIA MELALUI MODEL INKUIRI DI MA - Meri Yuniarsih (Manajer Pendididikan, 2016)
his study aims to determine whether the management of learning chemistry inquiry learning model can improve learning achievement and active students in class XI IPA MA Negeri2 Bengkulu City. From the data obtained an increase of student learning outcomes. In the first cycle, students who received grades completed KKM 65 20 students with a percentage of 62.5% increased to 23 people with a percentage of 71.8%. Data from observation of student activity increased from 60.6% in the first cycle to 69.1% in the second cycle. With the study of this classaction is successful so the researchers recommend preastasi inquiry model can improve student learning.Keywords: management, learning, inquiri, chemical